Direct and indirect landscape effects on Quercus ilex regeneration in heterogeneous environments. (Oecologia, 2012)
Understanding how plant-animal interactions shape plant regeneration is traditionally examined at local scales. In contrast, landscape ecologists working at regional scales often have to infer the mechanisms underlying vegetation patterns. In this study, we empirically explored how landscape attributes (patch connectivity, size, shape, irradiance, slope, and elevation) influence biotic interactions in 1- and 2-year seedlings and saplings of Quercus ilex. We combined field data and GIS-based information under a set of five connectivity scenarios, presuming low, intermediate, and long-distance seed dispersal. Our study emphasizes that landscape, apart from its direct effects on plants, plays a key, albeit indirect, role in plant demography through its effects on seed dispersers and predators. Moreover, the effects of landscape on recruitment differed between plant life stages. One-year seedlings and saplings appear to depend more on plant-animal interactions, while 2-year seedlings depend more on irradiance. Differences in patch connectivity resulted in direct and indirect effects on biotic interactions, which, in turn, produced contrasting positive and negative effects on regeneration at different stages of the life cycle. While jays and wild boars seem crucial to all life stages and most of the connectivity scenarios, rodents and herbivores affected only 1-year seedlings and saplings, respectively, and only a few of the connectivity scenarios. By simultaneously including an ensemble of explanatory factors, our study emphasizes that regeneration depends on a set of key drivers, both abiotic (i.e. irradiance) and biotic (i.e. jays and wild boars), whose effects are greatly modulated by landscape traits.

Spatial patterns in long-distance dispersal of Quercus ilex acorns by jays in a heterogeneous landscape (Ecography, 2003)
In this paper, I analyse the interaction between the holm-oak Quercus ilex, and one of its main dispersers, the European jay Garrulus glandarius, in an heterogeneous Mediterranean landscape. I quantify the spatial dispersal pattern of the seed shadow at two spatial scales, landscape (among patches) and microhabitat (within patches), by directly tracking the movement of seeds. Two main traits of the jay-mediated dispersal of holm-oak acorns across the landscape, the spatial pattern of dissemination and the distance from the source tree, are significantly and directly influenced by jay activity. Jays moved acorns nonrandomly, avoiding one main patch type of the study area to cache acorns, the shrubland-grasslands, and moving most of the acorns to pine stands, whether afforestation or open pinewoods. Within each patch type, jays had also a strong preference for caching acorns in some microhabitats, since>95% of the acorns dispersed by jays were cached beneath pines. The distance of holm-oak acorn dispersal was long in the study site, over 250 m, with some dispersals occurring up to 1 km from the source oaks. The shape of the dispersal kernel function fitted to the dispersal pattern produced by jays differed from those quantified for many other plant species. Jay-mediated dispersal had two components, one local and another produced by long-distance dispersal. Due to the heterogeneity of these Mediterranean environments, this difference in scale overlaps with a difference in habitat composition, short distances events resulting in dispersals within the same oak stands and long distance events resulting in dispersal outside of oak stands, usually to other vegetation units. Jay activity and movement pattern can have thus dramatic effects on both the local regeneration as well as the potential for regional spread of the holm-oak populations.